2022
DOI: 10.3390/separations9120397
|View full text |Cite
|
Sign up to set email alerts
|

Residual Characteristics of Atrazine and Its Metabolites in the Liaoning Province of China

Abstract: The simultaneous determination of atrazine residue and its metabolites was developed using liquid chromatography-tandem mass spectrometry in Liaoning Province, China. To ensure agricultural production and environmental safety, their contamination level was assessed. A total of 2142 samples were collected between 2014 and 2020, including 1213 soil samples, 190 surface water samples, and 739 groundwater samples. The overall pollution level and detectable level of the herbicides in Liaoning Province was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This mobility has been demonstrated in studies such as Vonberg et al 17 , which analyzed ATZ soil core residues from an agricultural field where ATZ had been applied before its ban in 1991, revealing an ATZ half-life value of about 2 years for the soil zone, significantly exceeding the highest ATZ half-lives found in the literature (433 days for subsurface soils). Similarly, Meng et al 18 observed the detection of ATZ in soil and surface water from 2014 to 2020, while hydroxyatrazine was found in soil without the selected analytes detected in groundwater. Additionally, ATZ bioaccumulation and biodegradation have been reported in some plants such as rice 19 and cattail 20 .…”
Section: Introductionmentioning
confidence: 79%
“…This mobility has been demonstrated in studies such as Vonberg et al 17 , which analyzed ATZ soil core residues from an agricultural field where ATZ had been applied before its ban in 1991, revealing an ATZ half-life value of about 2 years for the soil zone, significantly exceeding the highest ATZ half-lives found in the literature (433 days for subsurface soils). Similarly, Meng et al 18 observed the detection of ATZ in soil and surface water from 2014 to 2020, while hydroxyatrazine was found in soil without the selected analytes detected in groundwater. Additionally, ATZ bioaccumulation and biodegradation have been reported in some plants such as rice 19 and cattail 20 .…”
Section: Introductionmentioning
confidence: 79%
“…Triazine herbicides are extensively used as highly selective herbicides for controlling weeds in agricultural plants, mainly grasses [3]. However, they present the properties of good water solubility, a long half-life, relatively high mobility, and persistence in soils [4,5]. Therefore, their degradation, accumulation, toxicity, and hazards due to their environmental residues have caused considerable concern.…”
Section: Introductionmentioning
confidence: 99%